Two implementations of the preconditioned conjugate gradient method on heterogeneous computing grids - Collignon, Tijmen P.; Van Gijzen, Martin B. (Zielona Góra: Uniwersytet Zielonogórski)
Efficient iterative solution of large linear systems on grid computers is a complex problem. The induced heterogeneity andvolatile nature of the aggregated computational resources present numerous algorithmic challenges. This paper describesa case study regarding iterative solution of large sparse linear systems on grid computers within the software constraintsof the grid middleware GridSolve and within the algorithmic constraints of preconditioned Conjugate Gradient (CG) typemethods.
Keywords: grid computing; large sparse linear systems; iterative methods; conjugate gradient methods; Chronopoulos/Gear CG; GridSolve middleware; bubbly flows